Catchment-specific factors influencing isotopic variability of glacier melt and snowpack in the Himalayas - Dar, Tanveer; Rai, Nachiketa; Kumar, Sudhir (Frontiers in Water, 2025)
This study investigates the impact of catchment-specific environmental factors, such as aspect, albedo, and temperature, on isotopic variability in glacier melt and snowpack samples across three Himalayan catchments: Lidder, Sindh, and Rambiara. The findings reveal significant correlations between isotopic composition and environmental factors. Key predictors, particularly aspect and temperature, were identified, with R2 values indicating moderate to strong correlations. Aspect emerged as a primary factor influencing isotopic variability, especially in the Rambiara snowpack, where solar radiation exposure significantly shaped snow characteristics. In the Sindh catchment, the day of sampling (DOS) and temperature played crucial roles in isotopic variability, highlighting the importance of temporal and thermal factors. Albedo, reflecting surface radiation characteristics, was also found to influence isotopic composition in Sindh snow samples, likely affecting melt rates and snowpack stability. Altitude exhibited varying impacts across sample types and slopes. On the northern slopes of the Lidder catchment, glacier melt showed isotopic depletion with increasing elevation, typical of alpine glacial processes. Conversely, snow and snowpack samples on northern slopes exhibited moderate isotopic enrichment with altitude, likely influenced by wind redistribution and sublimation. In contrast, southern slopes showed minimal altitude influence on glacier melt and snow isotopic composition, with snowpacks at higher elevations showing moderate isotopic enrichment due to sublimation and partial melt processes. These findings underscore the complex interplay of environmental factors in shaping isotopic variability, emphasizing the need for high-resolution, catchment-specific studies. Future research should explore microclimatic conditions, wind redistribution, and snow metamorphism, as well as continuous monitoring and modeling efforts to enhance the understanding of isotopic trends and their implications for water resources in the Himalayan region.